2020
DOI: 10.1186/s12885-020-07412-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD28 in the prognosis of young lung adenocarcinoma patients

Abstract: Background The prognosis of lung cancer was found to be associated with a series of biomarkers related to the tumor immune microenvironment (TIME), which can modulate the biological behaviors and consequent outcomes of lung cancer. Therefore, establishing a prognostic model based on the TIME for lung cancer patients, especially young patients with lung adenocarcinoma (LUAD), is urgently needed. Methods In all, 809 lung cancer patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This finding indicates that the CD28 pathway may reverse the immuno-suppressive state. Furthermore, in lung adenocarcinoma, patients with high CD28 expression have lower disease-free survival (DFS) ( 20 ). The high expression of CD28 in the SD in our study was consistent with the above-mentioned conclusion, indicating that the high baseline status of CD28 might exhaust the ability of the co-stimulatory pathway to reverse immunosuppression, which led to the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the CD28 pathway may reverse the immuno-suppressive state. Furthermore, in lung adenocarcinoma, patients with high CD28 expression have lower disease-free survival (DFS) ( 20 ). The high expression of CD28 in the SD in our study was consistent with the above-mentioned conclusion, indicating that the high baseline status of CD28 might exhaust the ability of the co-stimulatory pathway to reverse immunosuppression, which led to the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, clinical significance analysis of CD28 in leukemia (ATL) revealed that patients with genetic abnormalities related to CD28 exhibited a worse prognosis than those without, indicating the beneficial effects of CD28 expression on the survival time of ATL patients (25). Controversially, the high expression of CD28 in lung cancer patients was associated with worse disease-free survival but a better overall survival (26). Thus, we speculated that CD28 might play a different role in the prognosis of different can-Besides, our results showed that the CD28 expression was significantly correlated with the number of CD4+ and CD8+ T-cells.…”
Section: Cd28 Is a Founding Member Of A Subfamily Of Costimulatory Mo...mentioning
confidence: 99%
“…It is likely that these cytotoxic cells are involved in the high morbidity of fibrotic interstitial lung diseases in patients with telomere dysfunction after a lung transplant. It seems that the status of CD28+ T cells behaves as a double-edged sword: an increase in CD28+ cells is tumorigenic in the early stage but related to more prolonged survival, and loss of CD28 is related to metastasis [ 111 , 112 ]. In contrast, a consequence of accumulating CD8+/CD28− T cells is that they can lose their function, have reduced expression of effector molecules (granzyme B and perforin), and reduced cytotoxic T-lymphocyte (CTL) activity [ 113 ].…”
Section: Influence Of Immune Cells With Shorter Telomeres On Development Of Lung Diseasesmentioning
confidence: 99%